Quantifying climate change impacts on future water resources and salinity transport in a high semi-arid watershed using the APEX-MODFLOW-Salt model - Balakrishnan, Jaya Vignesh, author; Bailey, Ryan, advisor; Arabi, Mazdak, advisor; Ronayne, Michael, committee member (Colorado State University. Libraries, 2023)
High salinity mobilization and movement from salt laden deposits in semi-arid landscape poses threat to impairment of soil and water resources worldwide. Semi-arid regions in the world are expected to experience rising temperatures and lower precipitation, which will impact water supply and likely spatio-temporal patterns of salinity loads affecting downstream water quality. No studies have evaluated salt fate and transport from high desert landscapes under the influence of future climate uncertainties. This study quantifies the impact of future climate change on hydrology and salinity transport and their total watershed yield in the Gunnison River Watershed (GRW) (14,608 km2), Colorado, using the APEX-MODFLOW-Salt hydro-chemical watershed model and three different CMIP5 climate models output downscaled by Multivariate Adaptive Constructed Analogs (MACA), each for two climate scenarios, RCP4.5, and RCP8.5, for the period 2020–2099. The APEX-MODFLOW-Salt model accounts for transport of hydrology and major salt ions (SO42-, Cl-, CO32-, HCO3-, Ca2+, Na+, Mg2+, and K+) to in-stream loading via various hydrological pathways (surface runoff, rainfall erosional runoff, soil lateral flow, quick return flow and groundwater discharge to streams). Results indicate that varying trends in precipitation output from different climate models with different RCP yields varying trends in annual average water yield (mm/ year) with predicted maximum and minimum change of +7.3% and -13.4% but annual average salinity loads (kg/year) discharged via watershed outlet simulation increased consistently with maximum and minimum change of +9.6% and +4.1% from the baseline scenario of 2007-2017. From the results, this conjunction of APEX-MODFLOW-Salt model with downscaled future climate forcings can be a helpful modeling framework for investigating hydrology and salt mobilization, transport, and export in both historical and predictive settings for salt-affected watersheds in the world.